Stable and clumped isotopes in desert carbonate spring and lake deposits reveal palaeohydrology: A case study of the Lower Jurassic Navajo Sandstone, south‐western USA. Issue 1 (13th December 2018) - Parrish, Judith Totman; Hyland, Ethan G.; Chan, Marjorie A.; Hasiotis, Stephen T.
Abstract: Carbon, oxygen and clumped isotope (Δ47 ) values were measured from lacustrine and tufa (spring)‐mound carbonate deposits in the Lower Jurassic Navajo Sandstone of southern Utah and northern Arizona in order to understand the palaeohydrology. These carbonate deposits are enriched in both 18 O and 13 C across the basin from east to west; neither isotope is strongly sensitive to the carbonate facies. However, 18 O is enriched in lake carbonate deposits compared to the associated spring mounds. This is consistent with evaporation of the spring waters as they exited the mounds and were retained in interdune lakes. Clumped isotopes (Δ47 ) exhibit minor systematic differences between lake and tufa‐mound temperatures, suggesting that the rate of carbonate formation under ambient conditions was moderate. These clumped isotope values imply palaeotemperature elevated beyond reasonable surface temperatures (54 to 86°C), which indicates limited bond reordering at estimated burial depths of ca 4 to 5 km, consistent with independent estimates of sediment thickness and burial depth gradients across the basin. Although clumped isotopes do not provide surface temperature information in this case, they still provide useful burial information and support interpretations of the evolution of groundwater locally. The findings of this study significantly extend the utility of combining stable isotope and clumped isotope methods into aeolian environments.